2011
DOI: 10.1111/j.1749-6632.2011.06181.x
|View full text |Cite
|
Sign up to set email alerts
|

To be or not to be: The self as illusion

Abstract: Moderated by Krista Tippett, creator and host of America Public Media's On Being, philosophers Thomas Metzinger (University of Mainz, Germany) and Evan Thompson (University of Toronto) join cardiologist and expert on near-death experiences Pim van Lommel (Hospital Rijnstate, the Netherlands) to examine recent developments in neuroscience and philosophy that shed light on whether our conscious experience of a unified self is reality or illusion. The following is an edited transcript of the discussion that occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…NDEs are described in many circumstances: cardiac arrest in myocardial infarction, shock, electrocution; coma resulting from traumatic brain damage; intracerebral hemorrhage or cerebral infarction; near-drowning or asphyxia; and apnea. [77][78][79][80][81][82] Although these results cannot simply be correlated with human experiment, it suggests the brain's remaining activity may explain the NDE. [77][78][79] As mentioned earlier from anecdotal observations, we occasionally found that when teaching CP to students, they relived their previous NDE experience during their CP.…”
Section: Hrv Assessment For Sce and Ndementioning
confidence: 99%
“…NDEs are described in many circumstances: cardiac arrest in myocardial infarction, shock, electrocution; coma resulting from traumatic brain damage; intracerebral hemorrhage or cerebral infarction; near-drowning or asphyxia; and apnea. [77][78][79][80][81][82] Although these results cannot simply be correlated with human experiment, it suggests the brain's remaining activity may explain the NDE. [77][78][79] As mentioned earlier from anecdotal observations, we occasionally found that when teaching CP to students, they relived their previous NDE experience during their CP.…”
Section: Hrv Assessment For Sce and Ndementioning
confidence: 99%